MICROFINANCE ACTIVITIES AND THEIR LONG-RUN IMPACT ON ECONOMIC GROWTH IN NIGERIA: EVIDENCE FROM ARDL ANALYSIS (1993-2023) - BiliqeesAyoola Abdulmumin, PhD (Gusau Journal of Accounting and Finance, 2025)
Microfinance has been globally recognized as a catalyst for economic growth, especially in developing economies such as Nigeria. Despite various efforts to improve access to finance, many low-income individuals and small enterprises remain excluded from the formal financial system. examines the effect of microfinance activities savings, lending, and investment on Nigeria's economic growth between 1993 and 2023, using secondary data from the Central Bank of Nigeria. The study employed the Autoregressive Distributed Lag (ARDL) model for the data analysis, the findings show that microfinance savings significantly boost GDP in the long run, while lending and investment exhibit statistically insignificant effects. Inflation and exchange rates negatively affect growth, while government expenditure has a significant positive influence. The study recommends strengthening savings mobilization, improving credit mechanisms, and implementing macroeconomic stabilization policies.